Recent Trends in Power Electronics for Renewable energy Systems - Ramya, M. V.; Ramya, G.; Thiruburasundari, V.; Ramadevi, N. (Journal of Electrical Engineering and Automation, 2022)
The complete world is focused on renewable power to reduce the global energy issue. Power electronic based energy conversion is being used extensively to improve the efficiency of the renewable energy conversion. It has a significant impact on the control and interface of renewable energy systems with both the network and stand-alone applications. As a result, increasing attention is being placed on the design and implementation of power converters. This study discusses the renewable energy systems (wind and solar) and the features of their energy conversion. The fundamental principles underlying their operations are discussed, as well as their recent technological advancements. It is a fact that power electronics is critical for interfacing and thus improving the system capacity.